Influence of partial submergence in exogenous ergothioneine on senescence and oxidative stress metabolism of broccoli during temperature abuse storage - Yan, Yifan; Bozzo, Gale G. (Frontiers in Horticulture, 2026)
Senescence of broccoli is accelerated with temperature abuse (i.e., exposure to warmer temperature than that considered optimal to preserve quality) in the postharvest supply chain. We investigated the impact of exogenous ergothioneine on the senescence of broccoli during temperature abuse storage. Broccoli heads were vertically oriented in immersion tanks so that the bottom of the stalk of each inflorescence was partially submerged in 0, 20, 100, or 500 µM ergothioneine prior to storage at 10°C for 10 days. Metabolite analysis revealed that the exogenous ergothioneine was taken up from the submergence solution and accumulated within the broccoli florets, with the greatest absorption in the 500 µM treatment. Floret yellowing due to chlorophyll loss was limited in broccoli treated with 20 µM ergothioneine relative to all other treatments. By the end of the storage period, H2O2 concentrations in the florets of 100 µM and 500 µM ergothioneine-treated broccoli matched those of the untreated broccoli and were up to 63% greater than the broccoli submerged under 20 µM ergothioneine. By the end of the storage period, broccoli treated with 20 µM ergothioneine had greater ratios of ascorbate/dehydroascorbate and glutathione/glutathione disulfide relative to all other treatments. Broccoli submerged in 20 µM ergothioneine had greater activities of glutathione reductase and dehydroascorbate reductase and a smaller increase in ascorbate peroxidase activity relative to the other pre-storage submergence treatments. The findings of this study provide a feasible postharvest handling strategy for the application of a critical 20 µM exogenous ergothioneine concentration that delays broccoli senescence during temperature abuse storage by preserving the status of endogenous antioxidants.